Human rights as the basic value of the concept of private law in modern Europe - Харитонов, Євген Олегович; Харитонов, Є. О.; Харитонов, Евгений Олегович; Kharytonov, Yevhen O.; Kharytonov, Evgen; Харитонова, Олена Іванівна; Харитонова, О. І.; Харитонова, Елена Ивановна; Kharytonova, Оlena I.; Харитонова, Тетяна Євгенівна; Харитонова, Т. Є.; Харитонова, Татьяна Евгеньевна; et al. (Universidad de la Amazonia, 2019)
The purpose of the article is a study of the concept and features of human rights as the fundamental concept of modern private law. The object of research is the historical, philosophical, political, ideological, economic, social and other dimensions of the concept of human rights. The main conclusion of the scientific article is the statement of the dominant role of the concept of human rights for the development of modern society, oriented to universal human liberal values and private law, as an indispensable attribute of such a society. At the same time, authors state, that modern tendencies for further expansion of the "borders" of human rights and freedoms at the expense of the interests of the state or at the expense of other social groups have no basis.

Метою статті є ґрунтовне дослідження поняття та ознак прав людини, як засадничої конструкції сучасного приватного права. Об’єктом дослідження є історичні, філософські, політичні, ідеологічні, економічні, соціальні та інші виміри концепції прав людини. Головним висновком наукової статті є констатування домінуючої ролі концепції прав людини для розвитку сучасного суспільства, що орієнтується на загальнолюдські ліберальні цінності та приватного права, як неодмінного атрибуту такого суспільства. При цьому, сучасні тенденції до подальшого розширення «меж» прав і свобод людини за рахунок інтересів держави або за рахунок інших соціальних груп не мають під собою жодних підстав.
Kharytonov E. Human rights as the basic value of the concept of private law in modern Europe / E. Kharytonov, O. Kharytonova, T. Kharytonova, D. Kolodin, Y. Tolmachevska // Universidad de la Amazonia, 2019. - Vol. 8. - Issue 20. - Р. 477-485.
Keywords: human rights; liberal economy; private law; Roman law; civil society; права людини; ліберальна економіка; приватне право; римське право; громадянське суспільство; Research Subject Categories::LAW/JURISPRUDENCE